Efficient processing method of biodegradable specialty paper

By using technologies such as agricultural waste and low melting point phase change materials, the problems of tight raw materials, single functions and environmental pollution in special paper production are solved, and efficient and low-cost biodegradable special paper processing is achieved, which improves the multiple properties and environmental protection of the paper.

CN119900191APending Publication Date: 2025-04-29FUJIAN MINQING SHUANGLING PAPER CO LTD
View PDF 0 Cites 0 Cited by

Patent Information

Application Number
CN202411750672.4
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-12-02
Publication Date
2025-04-29

AI Technical Summary

Technical Problem

The existing special paper production process has problems such as tight raw material resources, single functions, complex production process, high energy consumption and environmental pollution, which is difficult to meet the market's demand for high-performance environmentally friendly materials.

Method used

Agricultural waste is used as the main raw material, combined with low melting point phase change materials, microbubble injection, electric field-induced molding and dynamic hot pressing technologies to achieve efficient processing of biodegradable specialty paper.

Benefits of technology

It significantly reduces production costs, improves the mechanical properties, thermal insulation properties, waterproof properties of paper, etc., and realizes green and environmentally friendly and biodegradable special paper products to meet the market's demand for high-performance environmentally friendly materials.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119900191A_ABST
    Figure CN119900191A_ABST
Patent Text Reader

Abstract

The invention provides an efficient processing method of biodegradable specialty paper. The method comprises the following steps: S1, pretreating raw materials; s2, self-assembling and forming the fibers; s3, micro-bubble injection and dynamic hot press molding; S4, coating and curing; and S5, slitting and packaging. The invention provides an efficient processing method of green, environment-friendly and biodegradable specialty paper by taking agricultural wastes as main raw materials and combining technologies of a low-melting-point phase change material, microbubble injection, electric field induced molding, dynamic hot pressing and the like. According to the method, the production cost is greatly reduced, the mechanical property, the heat insulation performance, the waterproof performance and the like of the paper are remarkably improved, an economical and efficient solution is provided for development of the special paper industry, and the urgent requirement of the market for high-performance environment-friendly materials is met.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention relates to the technical field of paper manufacturing, in particular to a high-efficiency processing method for biodegradable special paper. Background Art

[0002] Specialty paper is a type of paper with special properties or functions, which is widely used in packaging materials, thermal insulation, high-performance printing, medical and health care, etc. However, the existing production process of specialty paper mainly relies on traditional wood pulping and chemical treatment methods, which have many technical and environmental problems:

[0003] Raw material resources are tight:

[0004] Most existing specialty papers use wood pulp as the main raw material, but the production of wood pulp consumes a large amount of forest resources, which is difficult to meet global environmental protection needs. In addition, the price of wood pulp fluctuates greatly, affecting the cost stability of the product. With the global emphasis on forest protection and the demand for sustainable development, finding low-cost, renewable non-wood raw materials has become a research hotspot.

[0005] Single function, low added value:

[0006] The functions of existing specialty papers are mostly concentrated on basic waterproof and oil-proof properties, lacking further functional expansion (such as heat insulation, waterproof, antibacterial, etc.). In high-performance demand scenarios (such as food preservation packaging, industrial insulation materials), existing specialty papers are often unable to meet complex application requirements due to their single function.

[0007] The production process is complex and energy-intensive:

[0008] The traditional production process of specialty paper requires multiple pulping, forming, coating and hot pressing processes, which are complex and energy-intensive. Especially in the forming and coating stages, the fibers are arranged randomly, making it difficult to achieve high mechanical properties and surface uniformity through simple processing.

[0009] Environmental pollution issues:

[0010] The preparation of wood pulp is accompanied by a large amount of wastewater and waste gas emissions, causing serious environmental pollution. Existing specialty papers often use plastic coatings or chemical enhancers, which are difficult to degrade naturally and eventually lead to plastic pollution after being discarded, increasing the ecological burden.

[0011] The contradiction between market demand and environmental protection trend:

[0012] With the popularization of green environmental protection and sustainable development concepts, the market has a strong demand for biodegradable materials. However, the existing specialty paper production relies on non-degradable plastics and traditional chemical coatings, which are gradually losing their advantages in market competition. Summary of the invention

[0013] In view of the shortcomings of the prior art, the present invention provides an efficient processing method for biodegradable specialty paper. With agricultural waste as the main raw material, combined with low melting point phase change materials, microbubble injection, electric field induced molding and dynamic hot pressing, an efficient processing method for green, environmentally friendly and biodegradable specialty paper is proposed. This method not only greatly reduces the production cost, but also significantly improves the mechanical properties, thermal insulation properties, and waterproof properties of paper, providing an economical and efficient solution for the development of the specialty paper industry and meeting the market's urgent demand for high-performance environmentally friendly materials.

[0014] To achieve the above objectives, the present invention is implemented by the following technical scheme: a highly efficient processing method for biodegradable specialty paper, the method comprising the following steps:

[0015] S1. Raw material pretreatment:

[0016] Crush agricultural waste raw materials to a particle size of ≤3mm;

[0017] At a temperature of 40-60°C, add cellulase at a mass ratio of 0.5%-1.5% for enzymatic hydrolysis for 4-6 hours;

[0018] Adjust the pH to 9–10, separate and recover lignin;

[0019] S2. Fiber self-assembly molding:

[0020] Add lignin or tannic acid crosslinking agent to the cellulose nanofiber suspension, with the mass ratio of the crosslinking agent being 5%–8% of the fiber suspension;

[0021] Adding 10% to 20% by weight of a biodegradable low melting point phase change material into the suspension;

[0022] The concentration of the suspension is adjusted to 1.5%-2.5%, and the fibers and the phase change material are oriented and arranged together to form a wet paper under the condition of an electric field strength of 0.5-1 kV / cm;

[0023] S3. Microbubble injection and dynamic hot pressing molding:

[0024] Add 10%-20% by mass of biodegradable microbubble particles with a particle size of 30-40 μm to wet paper;

[0025] During the dynamic hot pressing process, the wet paper is heated to the melting temperature of the low-melting-point phase change material, causing the phase change material to dynamically reorganize and form a self-supporting microstructure;

[0026] The paper is finally hot-pressed at 120–150°C and 5–10 MPa for 3–5 minutes.

[0027] S4. Coating and curing:

[0028] preparing a coating solution, the components of which include chitosan or alginate, and the concentration of the coating solution is 5%-10%;

[0029] Spray coating on the paper substrate surface with a thickness of 5–20 μm;

[0030] Dry the coated paper at 80–100°C for 1–2 minutes to cure the coating;

[0031] S5. Cutting and packaging:

[0032] The paper is cut to size and packaged using 100% biodegradable plant-based packaging materials.

[0033] The agricultural waste raw materials include one or more of rice husks, corn stalks, bagasse, wheat straw and coconut shell fibers.

[0034] Wherein, the cellulase is a composite enzyme preparation of cellulase and xylanase, and the enzymolysis time is preferably 5 hours.

[0035] Wherein, the low melting point phase change material is polycaprolactone or polybutylene succinate, and its melting temperature range is 50-70°C.

[0036] The electric field intensity of the electric field induced molding is preferably 0.8 kV / cm, and the concentration of the suspension is preferably 2%.

[0037] Wherein, the biodegradable microbubble particles are PLA microbubbles, starch-based microbubbles or lignin-based microbubbles, and the particle size thereof is preferably 30-40 μm.

[0038] The hot pressing temperature of the dynamic hot pressing molding is preferably 130° C., the pressure is preferably 7 MPa, and the hot pressing time is 4 minutes.

[0039] The coating liquid is prepared by mixing chitosan and sodium alginate in a mass ratio of 3:2, and its concentration is preferably 8%.

[0040] The coating is cured using UV light curing technology, with a light wavelength range of 200-400 nm and a curing time of 30-60 seconds.

[0041] Wherein, the packaging material is polylactic acid (PLA) film or starch-based packaging material, which is completely degradable and meets food-grade safety requirements.

[0042] The present invention provides an efficient processing method for biodegradable specialty paper, which has the following beneficial effects:

[0043] 1. High raw material utilization efficiency and low cost

[0044] The existing technology uses wood pulp as the main raw material, which is relatively expensive, consumes a lot of energy in the pulping process and has a significant impact on the environment.

[0045] The present invention uses agricultural wastes such as sugarcane bagasse, rice husks, corn stalks, etc. as main raw materials, which have low raw material cost, wide sources, and are in line with the trend of green environmental protection. Cellulose is efficiently extracted in the enzymatic hydrolysis step, and lignin is recovered as a by-product, with high resource utilization.

[0046] 2. Optimize fiber arrangement and improve mechanical properties

[0047] Existing technologies usually use traditional slurry forming, which results in disordered fiber arrangement, poor mechanical properties, and a tensile strength of only 35-37MPa.

[0048] The present invention introduces electric field induced molding technology, through the action of electric field, the fibers and low melting point phase change material molecules are oriented along the direction of the electric field to form a high-strength fiber network. The final tensile strength can reach 45MPa and the bending strength can reach 12MPa.

[0049] 3. Provide thermal insulation and add new functions

[0050] Ordinary wood pulp paper has no heat insulation function and poor thermal resistance (0.13–0.15m 2 ·K / W).

[0051] The present invention injects biodegradable microbubbles with a particle size of 20-50 μm into the paper to form a uniformly distributed thermal resistance layer, which improves the thermal insulation and the thermal resistance can reach 0.08 m 2 ·K / W.

[0052] 4. The coating has diversified functions and excellent waterproof and oil-proof performance

[0053] Ordinary wood pulp paper is uncoated or has a single coating, and its water absorption rate is usually above 20%.

[0054] The coating liquid of the present invention is prepared by chitosan or alginate, and a uniform functional coating is formed on the surface of the paper by combining the spraying technology, and the water absorption rate is reduced to 12%, and the paper has multiple functions such as antibacterial, waterproof and oil-proof.

[0055] 5. More environmentally friendly

[0056] Ordinary wood pulp paper usually uses plastic coatings or composite materials, which are difficult to fully degrade.

[0057] All raw materials and additives of the present invention are degradable materials (such as polycaprolactone, starch-based microbubbles, plant-based coatings, etc.), and both paper and packaging materials can be naturally degraded.

[0058] 6. Process optimization, higher efficiency

[0059] Traditional hot pressing processes cannot utilize the dynamic characteristics of phase change materials and usually require multiple steps to complete, resulting in a long production cycle.

[0060] The dynamic hot pressing molding technology of the present invention realizes the dynamic reorganization of the low melting point phase change material and the fiber solidification simultaneously, and has the advantages of short process time, low energy consumption and high production efficiency.

[0061] 7. Improve the surface quality of paper

[0062] Ordinary wood pulp paper has a high roughness (about 4.5μm) and poor surface uniformity.

[0063] The invention reduces the surface roughness of paper to 1.5 μm through coating and dynamic hot pressing treatment.

[0064] 8. Improvement of comprehensive economic and technical benefits

[0065] The present invention enables the special paper to achieve the best balance between cost and performance by introducing low-cost raw materials, high-performance coatings and functional designs.

[0066] In general, the technology of the present invention significantly improves the performance and functionality of biodegradable specialty paper. It not only far exceeds the existing technology in terms of mechanical properties, thermal insulation, waterproofness and other indicators, but also realizes green raw materials, efficient production and multifunctional products. Compared with the existing technology, the present invention is more economical and market-adaptable, and has a wide range of promotion value and competitive advantages. BRIEF DESCRIPTION OF THE DRAWINGS

[0067] Figure 1 It is a schematic diagram of the method flow of the present invention. DETAILED DESCRIPTION

[0068] The following will be combined with the drawings in the embodiments of the present invention to clearly and completely describe the technical solutions in the embodiments of the present invention. Obviously, the described embodiments are only part of the embodiments of the present invention, not all of the embodiments. Based on the embodiments of the present invention, all other embodiments obtained by ordinary technicians in this field without creative work are within the scope of protection of the present invention.

[0069] See also Figure 1 , a highly efficient processing method for biodegradable specialty paper, the method comprising the following steps:

[0070] S1. Raw material pretreatment:

[0071] The agricultural waste raw materials are crushed to a particle size of ≤3mm; the particle size of agricultural waste is reduced by mechanical crushing, the specific surface area is increased, and the contact efficiency between cellulase and fiber is improved. The small particle size also reduces the diffusion limitation during the enzymatic hydrolysis process and promotes the degradation of cellulose.

[0072] At a temperature of 40-60°C, cellulase is added at a mass ratio of 0.5%-1.5% for enzymatic hydrolysis for 4-6 hours; cellulase hydrolyzes the β-1,4-glycosidic bonds in cellulose and decomposes long-chain cellulose into short-chain cellulose, cellobiose and glucose. Xylanase can degrade hemicellulose components and release cellulose.

[0073] Adjust the pH to 9–10, separate and recover lignin; lignin dissolves in an alkaline environment (pH 9–10) to form lignin particles that can settle. At this time, cellulose remains suspended in the liquid phase.

[0074] 1. Material preparation and crushing: Process agricultural waste raw materials (such as rice husks, corn stalks, sugarcane bagasse, etc.) into a particle size suitable for subsequent enzymatic hydrolysis.

[0075] Specific steps:

[0076] ①Raw material collection and cleaning:

[0077] Collect agricultural waste (such as rice husks, corn stalks, sugarcane bagasse, etc.). Rinse with clean water to remove attached dirt and impurities. Dry in the air or use a low-temperature dryer (temperature not exceeding 60°C) to dry to a moisture content of less than 15%.

[0078] ② Crushing:

[0079] Use an industrial pulverizer (such as a hammer mill or a cutting mill) to crush the dried raw materials to a particle size of ≤3mm. Use screening equipment to grade them to ensure uniform particle size.

[0080] Key parameters:

[0081] Particle size: ≤3mm, which is convenient for the enzyme to contact with the raw materials during subsequent enzymatic hydrolysis.

[0082] Moisture content of raw materials: <15%, to avoid wet raw materials causing reduced crushing efficiency or equipment blockage.

[0083] 2. Enzymatic hydrolysis: Using cellulase to degrade complex polysaccharides in agricultural waste and release cellulose nanofibers.

[0084] Specific steps:

[0085] ①Prepare enzymatic solution:

[0086] Add an appropriate amount of water (liquid-to-solid ratio of 10:1 to 20:1) to the reaction tank. Add cellulase (such as cellulase, xylanase) at a mass ratio of 0.5%-1.5% (ratio of enzyme to dry raw material mass). Adjust the reaction temperature to 40-60℃ (optimal enzyme activity range).

[0087] ②Enzymatic hydrolysis process:

[0088] Add crushed agricultural waste to the enzymatic solution. Use a stirring device to maintain uniform mixing and prevent sedimentation. Control the enzymatic hydrolysis time to 4-6 hours, and take samples regularly during this period to test the slurry viscosity and fiber release.

[0089] ③Stop the enzyme reaction:

[0090] When the target degree of enzymatic hydrolysis is reached (cellulose conversion rate reaches more than 70%), the slurry is heated to 90° C. for 5 minutes to inactivate the enzyme activity.

[0091] Key parameters:

[0092] Temperature range: 40–60°C, controlled within the optimal activity range of cellulase.

[0093] Enzymatic hydrolysis time: 4–6 hours, depending on the fiber complexity of the raw material and the target degree of enzymatic hydrolysis.

[0094] Stirring speed: 100–200 rpm to ensure slurry homogeneity.

[0095] 3. Lignin separation and recovery: By adjusting the pH value, lignin in agricultural waste can be precipitated and recovered as a cross-linking agent or other by-products.

[0096] Specific steps:

[0097] ① Adjust pH value:

[0098] Slowly add alkaline solution (such as NaOH solution, concentration 5%-10%) to the slurry after enzymatic hydrolysis. Use a pH meter to monitor the pH value of the slurry and gradually adjust it to 9-10.

[0099] ② Lignin precipitation:

[0100] Allow the slurry to stand for 1–2 hours at a pH of 9–10 to observe the precipitation of lignin. Collect the settled lignin using a centrifuge or gravity separation equipment.

[0101] ③ Lignin cleaning and drying:

[0102] The settled lignin was washed with deionized water to remove impurities and dried in a dryer at 60–80°C to produce powdered lignin.

[0103] ④ Cellulose slurry retention:

[0104] After filtering to remove lignin, high-purity cellulose is retained in the slurry, which serves as the raw material for the subsequent steps.

[0105] Key parameters:

[0106] pH range: 9–10, ensuring that lignin precipitates under alkaline conditions.

[0107] Standing time: 1–2 hours to ensure that the lignin is fully settled.

[0108] Lignin recovery rate: ≥80%, ensuring resource utilization.

[0109] S2. Fiber self-assembly molding:

[0110] Lignin or tannic acid crosslinking agent is added to the cellulose nanofiber suspension, and the mass ratio of the crosslinking agent is 5%-8% of the fiber suspension; lignin or tannic acid forms crosslinks with the fiber surface through hydrogen bonds or electrostatic effects, thereby enhancing the connection strength between the fibers and constructing a preliminary network structure.

[0111] A biodegradable low-melting-point phase change material is added to the suspension at a mass ratio of 10%-20%; the low-melting-point phase change material (such as polycaprolactone and polybutylene succinate) melts during the subsequent heating process, filling the gaps in the fiber network, and solidifies during cooling to form a reinforced structure.

[0112] The concentration of the suspension is adjusted to 1.5%-2.5%, and under the condition of an electric field strength of 0.5-1kV / cm, the fibers and the phase change material are oriented together to form a wet paper; under the action of the electric field, the polar molecules of the cellulose nanofibers and the phase change material are rearranged along the direction of the electric field to form an oriented arrangement. The electrophoresis and dielectrophoresis effects further make the fibers evenly distributed and reduce agglomeration.

[0113] 1. Preparation of cellulose nanofiber suspension: Prepare a uniform cellulose nanofiber (CNF) suspension to lay the foundation for the subsequent addition of cross-linking agent and phase change material.

[0114] step:

[0115] ①Fiber pulp dilution:

[0116] The cellulose slurry obtained from step S1 was adjusted to a concentration of 1.5%-2.5%, diluted with deionized water and stirred evenly.

[0117] ②Nano-processing:

[0118] Using a high-pressure homogenizer (pressure range: 30-60MPa), cellulose microfibrils are transformed into nanofibers through multiple cycles (usually 3-5 times), resulting in a stable cellulose nanofiber suspension with moderate viscosity and no large particle impurities.

[0119] Key parameters:

[0120] Suspension concentration: 1.5%–2.5%.

[0121] Nanofiber diameter: 10–50 nm.

[0122] Number of homogenizer cycles: 3–5 times.

[0123] 2. Add cross-linking agent: The strength and stability of the fiber network structure are enhanced by cross-linking agent.

[0124] step:

[0125] ①Select cross-linking agent:

[0126] Use lignin (powder) or tannic acid (solution) as crosslinking agent. Add 5%–8% of the total mass of the fiber suspension.

[0127] ②Mix evenly:

[0128] Slowly add the crosslinking agent to the fiber suspension and stir with a slow stirrer (50-100 rpm) for 10 minutes to ensure uniform dispersion. Let stand for 30 minutes to ensure initial crosslinking reaction.

[0129] Key parameters:

[0130] Cross-linking agent ratio: 5%-8% (based on the mass of fiber suspension).

[0131] Stirring time: 10 minutes, standing time: 30 minutes.

[0132] Reaction temperature: room temperature (20–25°C).

[0133] 3. Add low-melting-point phase change materials: Phase change materials are used to give paper special functionality and form a composite microstructure with the fiber network.

[0134] step:

[0135] ①Select phase change material:

[0136] Select polycaprolactone (PCL) or polybutylene succinate (PBS), and choose granular or emulsion materials according to product requirements. The proportion of phase change material is 10%-20% of the total mass of the fiber suspension.

[0137] ②Material dispersion:

[0138] Preheat the phase change material to 50-70°C (close to its melting temperature) and disperse it in deionized water to form a stable emulsion. Slowly drip the emulsion into the fiber suspension and disperse it using a high-speed disperser (speed 300-500rpm) for 15 minutes.

[0139] Key parameters:

[0140] Phase change material ratio: 10%–20%.

[0141] Dispersion temperature: 50–70°C.

[0142] Dispersion time: 15 minutes.

[0143] 4. Electric field induced directional alignment: The electric field is used to coordinately align the cellulose nanofibers and the phase change material to form high-performance wet paper.

[0144] step:

[0145] ① Equipment preparation:

[0146] A flat-plate electric field induction molding device is used, including two upper and lower electrode plates and a suspension tank. The electrode spacing is 5-10 mm. A high-voltage power supply is connected, and the electric field strength is set to 0.5-1 kV / cm.

[0147] ②Molding operation:

[0148] Pour the cellulose suspension into the forming tank with a thickness of 3-5 mm. Start the electric field so that the electric field force acts on the charged fibers and phase change material molecules in the suspension. Let it stand for 5-10 minutes and observe the fibers and phase change material aligning along the direction of the electric field to form the prototype of wet paper.

[0149] ③Drainage and solidification:

[0150] Turn off the electric field and transfer the initially formed wet paper to the vacuum dehydration equipment to remove excess water. Maintain the integrity of the wet paper before entering the next step of dynamic hot pressing.

[0151] Key parameters:

[0152] Electric field strength: 0.5–1 kV / cm.

[0153] Electrode spacing: 5–10 mm.

[0154] Resting time: 5–10 minutes.

[0155] S3. Microbubble injection and dynamic hot pressing molding:

[0156] Add 10%-20% of biodegradable microbubble particles with a particle size of 30-40μm to wet paper; the microbubbles are embedded in the fiber network through capillary action and interfacial effect. Its stable bubble structure plays a role in lightening and heat insulation during hot pressing.

[0157] During the dynamic hot pressing process, the wet paper is heated to the melting temperature of the low-melting-point phase change material, causing the phase change material to dynamically reorganize and form a self-supporting microstructure; the low-melting-point phase change material is heated to 50-70°C to melt, flow to fill the gaps in the fiber network, and dynamically reorganize to form a dense microstructure. When cooled, the phase change material solidifies and stabilizes the microstructure.

[0158] The paper is finally hot-pressed at 120–150°C and 5–10 MPa for 3–5 minutes; the high temperature and pressure further compress the fiber network and microbubbles, solidify the phase change material, and ensure the overall strength and stability of the paper.

[0159] 1. Microbubble injection: evenly distribute biodegradable microbubble particles to improve the lightweight and thermal insulation properties of paper.

[0160] step:

[0161] ①Prepare microbubble dispersion:

[0162] Select biodegradable microbubble particles, such as PLA microbubble, starch-based microbubble or lignin-based microbubble, with a particle size range of 30-40 μm. Mix the microbubble particles with water or fiber suspension at a mass ratio of 10%-20%, and stir with a high-speed stirrer for 10-15 minutes to form a uniform dispersion.

[0163] ② Microbubbles dispersed onto wet paper:

[0164] Place the wet paper in a coating machine or injection device and introduce the microbubble dispersion evenly into the wet paper by spraying or dipping. Control the spraying amount or dipping time (1-3 minutes) to ensure that the microbubbles are evenly distributed in the fiber network of the wet paper.

[0165] Key control parameters:

[0166] Microbubble particle size: 30–40 μm, ensuring that the particle size fits the pore structure of the fiber network.

[0167] Microbubble ratio: 10%–20%, taking into account both lightweight effect and material strength.

[0168] Dispersion uniformity: Avoid microbubble aggregation through high-speed stirring or ultrasonic treatment.

[0169] 2. Dynamic hot pressing: Through hot pressing and phase change process, the phase change material is reorganized to form a microstructure with self-supporting ability.

[0170] step:

[0171] ①Preliminary heating (dynamic phase change):

[0172] The wet paper after microbubble injection is placed in a hot press and initially heated to 50–70°C (the melting temperature range of low-melting phase change materials). During the heating process, the low-melting phase change material (such as polycaprolactone or polybutylene succinate) changes from a solid state to a molten state, and its fluidity is enhanced. While heating, a low pressure (1–2MPa) is maintained to allow the phase change material to fill the pores between the fibers and form a composite structure with the microbubble particles.

[0173] ② Dynamic reorganization and finalization:

[0174] As the phase change material melts and the microbubbles expand, a uniform supporting microstructure gradually forms in the fiber network. During the dynamic phase change process, a slow pressure increase (reaching the target pressure within 2-5 minutes) is used to ensure the stability of the microstructure and avoid local damage.

[0175] Key control parameters:

[0176] Initial heating temperature: 50–70°C, keep the phase change material in a molten state.

[0177] Initial pressure: 1–2 MPa, to prevent premature solidification resulting in insufficient flow of phase change materials.

[0178] Heating time: 3–5 minutes to ensure that the phase change material is fully distributed and forms a stable connection with the fiber network.

[0179] 3. Final hot pressing: Through high temperature and high pressure, the paper structure is solidified and its performance is optimized.

[0180] step:

[0181] ① Heating and hot pressing:

[0182] After the initial heating, the wet paper is further heated to 120–150°C (a temperature range suitable for paper strength and PCM curing). At the same time, high pressure (5–10 MPa) is applied to cure the PCM in the fiber network and compact the microbubble structure, improving the strength and lightweight performance of the paper.

[0183] ②Cooling and demoulding:

[0184] After the heat press is complete, gradually lower the temperature (to room temperature within 30–60 seconds) to allow the phase change material to solidify and set. Remove the formed paper from the heat press to ensure there is no noticeable warping or delamination.

[0185] Key control parameters:

[0186] Hot pressing temperature: 120–150°C, to achieve synergistic curing effect of fiber and coating.

[0187] Hot pressing pressure: 5-10MPa, to ensure the density and overall strength of the fiber network.

[0188] Hot pressing time: 3–5 minutes to prevent the microbubble structure from collapsing or the material from overheating.

[0189] S4. Coating and curing:

[0190] Prepare a coating liquid, whose components include chitosan or alginate, and the coating liquid concentration is 5%-10%; spray the coating on the surface of the paper base, and the spraying thickness is 5-20μm; the coating liquid is evenly distributed on the surface of the paper through capillary action, and the chitosan or alginate forms hydrogen bonds with the fiber. Coating additives (such as plasticizers, antibacterial agents) further enhance the functionality of the coating.

[0191] The coated paper is dried at 80–100°C for 1–2 minutes to cure the coating; the chitosan is dehydrated and cured during the heating process, forming a stable bond with the fiber matrix. The alginate is cured into a uniform film after removing excess water through thermal evaporation.

[0192] 1. Preparation of coating liquid: Prepare uniform and stable coating liquid to provide paper with waterproof, oil-proof or antibacterial functions.

[0193] step:

[0194] ①Select coating material:

[0195] Chitosan coating: Chitosan is a natural polysaccharide that provides antibacterial and water-resistant properties. Alginate coating: Sodium alginate has good film-forming properties and flexibility, making it suitable for food packaging.

[0196] ②Prepare coating liquid:

[0197] Chitosan solution: Add 1%–3% acetic acid to deionized water and adjust the pH to 4–6. Add chitosan powder gradually at a concentration of 5%–10% and stir until completely dissolved to form a transparent solution. Sodium alginate solution: Dissolve sodium alginate directly in deionized water at a concentration of 5%–10%. Use ultrasonic oscillation (20–30 minutes) to disperse and ensure that the solution is bubble-free and uniform.

[0198] ③Optimize coating function (optional):

[0199] Add functional additives: such as nano-silicon dioxide (SiO2, to enhance barrier properties), plant-derived antimicrobial agents, or plasticizers (such as glycerol, to enhance flexibility). Mix well: stir at high speed (300-500rpm) for 10-15 minutes.

[0200] Key parameters:

[0201] Coating liquid concentration: 5%–10%.

[0202] pH value: 4–6 for chitosan solution.

[0203] Stirring time: 10–15 minutes to ensure a homogenous solution.

[0204] 2. Coating: Apply the coating liquid evenly on the paper surface to reach the specified thickness.

[0205] step:

[0206] ①Coating method:

[0207] Spraying method: Use an automatic sprayer to evenly spray the coating liquid onto the paper surface. Spraying pressure: 2-5 bar, the spraying speed is adjusted according to the paper moving speed.

[0208] Blade coating: Using a blade coater, the coating thickness is controlled by the blade gap. The blade gap is set to 5–20 μm.

[0209] ②Control coating thickness:

[0210] Monitor coating thickness in real time to ensure it is within the range of 5–20 μm. For spraying, coating uniformity can be controlled by adjusting the spray liquid flow rate or nozzle diameter.

[0211] ③Double-sided coating (optional):

[0212] If necessary, when both sides of the paper need to be coated, a double-sided spraying device can be used to ensure that the coating thickness on both sides is consistent.

[0213] Key parameters:

[0214] Coating thickness: 5–20 μm.

[0215] Spraying pressure: 2–5 bar.

[0216] Coating method: spraying or scraping, the choice depends on the paper function requirements and equipment configuration.

[0217] 3. Drying and curing: Fix the coating by heating and drying to improve paper functionality and coating stability.

[0218] step:

[0219] ①Pre-drying:

[0220] The coated paper is placed in a forced air drying device at a temperature of 80–100°C. The drying time is 1–2 minutes to remove surface moisture.

[0221] ②Curing treatment:

[0222] For chitosan coating, thermal curing (temperature 80–100°C) is used to make the coating firmly bonded to the paper substrate. For sodium alginate coating, UV light curing (wavelength 200–400nm, time 30–60 seconds) can be used to enhance the hardness of the coating after drying.

[0223] ③Cooling and shaping:

[0224] After curing is complete, use cooling equipment (such as a blower or cooling belt) to reduce the paper temperature to room temperature. Avoid warping of hot paper and ensure that the coating is uniform and stable.

[0225] Key parameters:

[0226] Drying temperature: 80–100°C.

[0227] Drying time: 1–2 minutes.

[0228] UV light curing time (optional): 30–60 seconds.

[0229] 4. Inspection: Ensure that the coating uniformity, thickness and functionality meet the design requirements.

[0230] Detection method:

[0231] Coating thickness detection: Use an electron microscope or laser thickness gauge to measure the average thickness and uniformity of the coating.

[0232] Functional testing:

[0233] Waterproofness: dripping water contact angle test (contact angle ≥90° is qualified for waterproofness). Antibacterial property (for chitosan coating): antibacterial effect is tested using colony counting method.

[0234] S5. Cutting and packaging:

[0235] The paper is cut to size and packaged using 100% biodegradable plant-based packaging materials.

[0236] Furthermore, the cellulase is a composite enzyme preparation of cellulase and xylanase, and the enzymolysis time is preferably 5 hours.

[0237] Furthermore, the low melting point phase change material is polycaprolactone or polybutylene succinate, and its melting temperature range is 60°C.

[0238] Furthermore, the electric field intensity of the electric field induced molding is preferably 0.8 kV / cm, and the concentration of the suspension is preferably 2%.

[0239] Wherein, the biodegradable microbubble particles are PLA microbubbles, starch-based microbubbles or lignin-based microbubbles, and the particle size thereof is preferably 30-40 μm.

[0240] Furthermore, the hot pressing temperature of the dynamic hot pressing molding is preferably 130° C., the pressure is preferably 7 MPa, and the hot pressing time is 4 minutes.

[0241] Furthermore, the coating liquid is prepared by mixing chitosan and sodium alginate in a mass ratio of 3:2, and its concentration is preferably 8%.

[0242] Furthermore, the coating is cured using UV light curing technology, with a light wavelength range of 300 nm and a curing time of 40 seconds.

[0243] Furthermore, the packaging material is a polylactic acid (PLA) film or a starch-based packaging material, which is completely degradable and meets food-grade safety requirements.

[0244] The following is a summary table of comparative tests and test results based on the present invention:

[0245]

[0246]

[0247] All papers were prepared in a standardized manner and cut into standard sizes (100 mm×100 mm). Environmental conditions: room temperature 25° C., relative humidity 50%.

[0248] Test indicators:

[0249] Tensile strength: measured by electronic tensile testing machine, unit: MPa.

[0250] Thermal insulation: Thermal resistance measured by the steady-state plate method, unit: m 2 ·K / W.

[0251] Water absorption rate: the percentage of paper weight increase after soaking for 10 minutes.

[0252] Bending strength: three-point bending test, unit: MPa.

[0253] Surface roughness: detected by laser microscope, unit: μm.

[0254] Data Analysis:

[0255] Tensile strength: The highest tensile strength of test 6 is 45MPa, which is significantly higher than the mainstream product (37MPa). This is attributed to the electric field induced alignment and dynamic reorganization of the phase change material, which enhances the bonding force of the fiber network.

[0256] Thermal insulation: The thermal insulation of the present invention is at least 0.08m 2 K / W, the highest for mainstream products is 0.15m 2 ·K / W. The thermal resistance effect of micro-bubble filling significantly improves the thermal insulation performance.

[0257] Water absorption rate: The minimum water absorption rate of the present invention is 12%, while that of mainstream products is 25%. The chitosan / alginate coating significantly improves the waterproof performance.

[0258] Bending strength: The highest bending strength of the present invention is 12MPa, while the mainstream product is only 8MPa. The dynamic hot pressing process improves the structural stability.

[0259] Surface roughness: The minimum surface roughness of the present invention is 1.5 μm, while the mainstream product is as high as 4.5 μm, which shows that the coating process of the present invention is more sophisticated.

[0260] in conclusion:

[0261] Performance advantages: The present invention is superior to mainstream products in terms of tensile strength, thermal insulation, waterproofness, bending resistance and surface uniformity.

[0262] Mechanism verification: Core processes such as electric field induction, microbubble injection and dynamic hot pressing effectively improve the functionality of paper.

[0263] Promotion value: The present invention is suitable for high-demand packaging, heat insulation and waterproof application scenarios and has broad industrial prospects.

[0264] Although embodiments of the present invention have been shown and described, it will be appreciated by those skilled in the art that various changes, modifications, substitutions and variations may be made to the embodiments without departing from the principles and spirit of the present invention, and that the scope of the present invention is defined by the appended claims and their equivalents.

Claims

1. A highly efficient processing method for biodegradable specialty paper, characterized in that: The method comprises the following steps: S1. Raw material pretreatment: Crush agricultural waste raw materials to a particle size of ≤3mm; At a temperature of 40-60°C, add cellulase at a mass ratio of 0.5%-1.5% for enzymatic hydrolysis for 4-6 hours; Adjust the pH to 9–10, separate and recover lignin; S2. Fiber self-assembly molding: Add lignin or tannic acid crosslinking agent to the cellulose nanofiber suspension, with the mass ratio of the crosslinking agent being 5%–8% of the fiber suspension; Adding 10% to 20% by weight of a biodegradable low melting point phase change material into the suspension; The concentration of the suspension is adjusted to 1.5%-2.5%, and the fibers and the phase change material are oriented and arranged together to form a wet paper under the condition of an electric field strength of 0.5-1 kV / cm; S3. Microbubble injection and dynamic hot pressing molding: Add 10%-20% by mass of biodegradable microbubble particles with a particle size of 30-40 μm to wet paper; During the dynamic hot pressing process, the wet paper is heated to the melting temperature of the low-melting-point phase change material, causing the phase change material to dynamically reorganize and form a self-supporting microstructure; The paper is finally hot-pressed at 120–150°C and 5–10 MPa for 3–5 minutes. S4. Coating and curing: preparing a coating solution, the components of which include chitosan or alginate, and the concentration of the coating solution is 5%-10%; Spray coating on the paper substrate surface with a thickness of 5–20 μm; Dry the coated paper at 80–100°C for 1–2 minutes to cure the coating; S5. Cutting and packaging: The paper is cut to size and packaged using 100% biodegradable plant-based packaging materials.

2. The efficient processing method of biodegradable specialty paper according to claim 1, characterized in that: The agricultural waste raw materials include one or more of rice husks, corn stover, bagasse, wheat straw and coconut shell fiber.

3. The efficient processing method of biodegradable specialty paper according to claim 1, characterized in that: The cellulase is a composite enzyme preparation of cellulase and xylanase, and the enzymolysis time is preferably 5 hours.

4. The efficient processing method of biodegradable specialty paper according to claim 1, characterized in that: The low melting point phase change material is polycaprolactone or polybutylene succinate, and its melting temperature range is 50-70°C.

5. The efficient processing method of biodegradable specialty paper according to claim 1, characterized in that: The electric field intensity of the electric field induced molding is preferably 0.8 kV / cm, and the concentration of the suspension is preferably 2%.

6. The efficient processing method of biodegradable specialty paper according to claim 1, characterized in that: The biodegradable microbubble particles are PLA microbubbles, starch-based microbubbles or lignin-based microbubbles, and the particle size thereof is preferably 30-40 μm.

7. The efficient processing method of biodegradable specialty paper according to claim 1, characterized in that: The hot pressing temperature of the dynamic hot pressing molding is preferably 130° C., the pressure is preferably 7 MPa, and the hot pressing time is 4 minutes.

8. The efficient processing method of biodegradable specialty paper according to claim 1, characterized in that: The coating liquid is prepared by mixing chitosan and sodium alginate in a mass ratio of 3:2, and its concentration is preferably 8%.

9. The efficient processing method of biodegradable specialty paper according to claim 1, characterized in that: The coating is cured by UV light curing technology, with a light wavelength range of 200-400 nm and a curing time of 30-60 seconds.

10. The efficient processing method of biodegradable specialty paper according to claim 1, characterized in that: The packaging material is a polylactic acid film or a starch-based packaging material, which is completely degradable and meets food-grade safety requirements.